2015
DOI: 10.1155/2015/768352
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Superoxide Monitoring ofIn VitroNeuronal Differentiation Using a Cell-Based Biosensor

Abstract: Membrane-engineered cells bearing superoxide dismutase (SOD) molecules on their surface offer the capability of ultrarapid and ultrasensitive detection of the superoxide anion (O2-) through the measurement of changes of their cell membrane potential. We herewith report the application of this technology for the noninvasive determination of superoxide levels during thein vitrodifferentiation of PC12 cells. We were able to detect changes inO2-accumulation in the culture medium, which were closely associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Cells were immobilized in calcium alginate, forming beads containing 75 × 10 3 cells per bead with an approximate diameter of 2 mm. As already reported [39,43], the membrane potential of membrane-engineered Vero cell fibroblasts is affected by the interactions of electroinserted SOD molecules and superoxide anions, producing measurable changes in the membrane potential.…”
Section: Creation Of Membrane-engineered Cells and Bioensor Fabricatisupporting
confidence: 57%
See 1 more Smart Citation
“…Cells were immobilized in calcium alginate, forming beads containing 75 × 10 3 cells per bead with an approximate diameter of 2 mm. As already reported [39,43], the membrane potential of membrane-engineered Vero cell fibroblasts is affected by the interactions of electroinserted SOD molecules and superoxide anions, producing measurable changes in the membrane potential.…”
Section: Creation Of Membrane-engineered Cells and Bioensor Fabricatisupporting
confidence: 57%
“…A cell-bearing bead was attached to the working electrode while a cell-free bead was connected to the reference electrode. For each assay, both beads (sensor system, Figure 1) were immersed into the well containing adherent cells [39] and the response of each biosensor potential was achieved within 100 s after its sinking into the culture medium. The biosensor was calibrated with known superoxide concentration produced by the oxidation of xanthine by the xanthine oxidase.…”
Section: Biosensor Setup For Recording Superoxide Concentration and Dmentioning
confidence: 99%
“…Live cell-fluorescent biosensors allow the collection of temporal information about cellular events, from changes of the membrane potential of the cell till cell cycle progression and arrest. Measuring the changes of cell membrane potential, the level of superoxide anion generated during the in vitro differentiation of PC-12 cells was determined in a noninvasive way [ 73 ]. Nevertheless, using a fluorescent biosensor, it was demonstrated that NGF-induced neurite extension occurs independently of NGF-induced cell cycle G1 phase arrest.…”
Section: Cellular Eventsmentioning
confidence: 99%
“…Among these techniques, a system of measuring the change in electrical potential (or other electrical properties) of a single cell membrane or singlecell segment has been developed at the tissue level. Bioelectric Recognition Assay (BERA) is a method for detection of bioactive substances based on the measurement of electrical properties of a cell group, and to date has been used in many applications, such as recently, for the determination of peroxide levels by PC12 cells in vitro (Moschopoulou & Kintzios, 2015). Although many electrophysiological methods such as single-unit recording (Wuttke et al, 2003) and the patch-clamp technique (Carmichael, 2008) have been developed to date, the BERA method has advantages over these methods because of its ability to detect analytes in a specific, fast (less than 3 minutes) way, remarkably reproducible and economical.…”
Section: Introductionmentioning
confidence: 99%